A Low‐Delay MDCT/IMDCT. Issue 5 (1st October 2013) - Lee, Sangkil; Lee, Insung
Abstract : This letter presents an algorithm for selecting a low delay for the modified discrete cosine transform (MDCT) and inverse MDCT (IMDCT). The implementation of conventional MDCT and IMDCT requires a 50% overlap‐add (OLA) for a perfect reconstruction. In the OLA process, an algorithmic delay in the frame length is employed. A reduced overlap window and MDCT/IMDCT phase shifting is used to reduce the algorithmic delay. The performance of the proposed algorithm is evaluated by applying the low‐delay MDCT to the G. 729.1 speech codec.